Analisis Epistemologi Pendidikan Islam di SMP El Dzikir Bulu Sukoharjo: Peran Pengetahuan Al Qur’an dan Hadits dalam Kurikulum - Mujiburrahman Mujiburrahman; Abu Husein Ibrahim Al ‘ithriy (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
integrating revealed knowledge with the demands of modern education. At SMP El Dzikir Bulu Sukoharjo, the Qur’an and Hadith are positioned as the primary sources of knowledge in the curriculum, yet their epistemological role requires deeper analysis. This research aims to examine the epistemology of Islamic education and the role of the Qur’an and Hadith in the formulation and implementation of the school curriculum. The study employs a descriptive qualitative approach. Data were collected through in-depth interviews with the principal, vice principal for curriculum, and Islamic education teachers, supported by observations and document analysis. The data were analyzed using a descriptive-interpretative method. The findings reveal that the educational epistemology at SMP El Dzikir is based on a non-dichotomous paradigm integrating naqli (revelation-based) and aqli (reason-based) knowledge. The Qur’an functions as the primary source of knowledge, while the Hadith serves as its interpreter in shaping curriculum and learning, leading to a holistic Islamic education oriented toward the formation of rabbani character.